Effect of Aquo-glycolic Media and Added Anions on the Anodization of Zircaloy-4 in Sulphamic Acid - Viplav Duth Shukla; CH. Anjaneyulu (E-Journal of Chemistry)
Anodization of zircaloy-4 in 0.1 M sulphamic acid has been carried out. Kinetics of anodic oxidation of zircaloy-4 has been studied at a constant current density of 8 mA/cm2 and at room temperature. Thickness estimates were made from capacitance data. The plots of formation voltage vs. time, reciprocal capacitance vs. time, reciprocal capacitance vs. formation voltage and thickness vs. formation voltage were drawn and rate of formation, current efficiency and differential field were calculated. The addition of solvent (ethylene glycol) showed better kinetic results. For 25%, 50% and 75% aquo-glycolic media, the dielectric constant values are low leading to a marked improvement in the kinetics. In 80% ethylene glycol, though the dielectric constant value of solution is less, the kinetics was slow which may be attributed to the fact that the electrolyte becomes highly non-polar. Improvement in the kinetics of oxide film formation was observed by the addition of millimolar concentration of anions (CO32-, SO42-, PO43-). The presence of phosphate ions improved the kinetics of anodization to better extent.